Non-coding RNAs in pluripotency and neural differentiation of human pluripotent stem cells - Lukovic, Dunja; Moreno-Manzano, Victoria; Klabusay, Martin; Stojkovic, Miodrag; Bhattacharya, Shomi S.; Erceg, Slaven (Frontiers in Genetics, 2014)
Several studies have demonstrated the important role of non-coding RNAs as regulators of posttranscriptional processes, including stem cells self-renewal and neural differentiation. Human embryonic stem cells (hESCs) and induced pluripotent stem cells (ihPSCs) show enormous potential in regenerative medicine due to their capacity to differentiate to virtually any type of cells of human body. Deciphering the role of non-coding RNAs in pluripotency, self-renewal and neural differentiation will reveal new molecular mechanisms involved in induction and maintenances of pluripotent state as well as triggering these cells toward clinically relevant cells for transplantation. In this brief review we will summarize recently published studies which reveal the role of non-coding RNAs in pluripotency and neural differentiation of hESCs and ihPSC.